Estudo e implementação computacional de sistema de armazenamento de energia com conexão direta ao sistema elétrico - Dias, Camila de Oliveira (2020)
At this moment, the electrical power system, worldwide, is undergoing an important paradigm shift, which is based on three pillars: decarbonization, digitalization and decentralization. Decarbonization is directly connected to the replacement of energy sources from fossil fuels, responsible for the emission of gases that potentiate the greenhouse effect, by renewable sources, mainly of wind and solar nature. Meanwhile, digitization occurs due to the insertion of a strong monitoring framework in the grid, which is coupled with a large increase in the communication and control systems, making operation and monitoring possible in realtime. Decentralization, on the other hand, is in line with the emergence of distributed generation, microgrids and, also, energy storage. In this context, from then on, there has been a continuous increase in the importance of electrical energy storage systems, especially those composed of batteries. Its insertion in the grid is linked to different benefits to the three levels of the system: generation, transmission and distribution. Such storage systems provide increased grid autonomy, independence and reliability. In this way, considering its expansion, as well as anticipating the impacts of its future connection to the power system, investigative studies about the main existing technologies applied to this finality are necessary, including aspects related to hardware, materials and control. In this context, the work in question aims to explore and deepen general aspects related to different energy storage strategies, focusing in particular on storage systems consisting of batteries with direct connection to the grid. Thus, a complete modeling of the storage system, with emphasis on the charging and discharging processes, is carried out, and the results are properly presented and discussed. In addition, this modeling also aims to enable an extensive range of studies, as well as future analyzes in several areas of electrical engineering, such as electrical power systems, energy efficiency, smart grids and power quality.